EMPLOYEE JOB SATISFACTION: IN TERMS OF ANALYSIS OF JOB DESCRIPTION AND ORGANIZATIONAL CULTURE OF DINAS PENDIDIKAN KOTA MALANG - Suyitno; Sudarjo (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2025)
The purpose of this study was to determine and analyze the influence of job description and organizational culture both partially and simultaneously on employee job satisfaction at the Dinas Pendidikan Kota Malang. This study used a quantitative approach using the explanatory survey method with a sample of 76 respondents who were employees of the Dinas Pendidikan Kota Malang. Data processing was carried out using the assistance of IBM SPSS Statistics 24. The study found that (1) The job description variable has a significant effect on employee job satisfaction with an influence value of 68%. (2) The organizational culture variable has a significant effect on employee job satisfaction with an influence value of 44.2%. Simultaneously, the job description and organizational culture variables have a significant effect on employee job satisfaction at the Dinas Pendidikan Kota Malang.